Seoul Republic of Korea august 21 - 26, 1989 (Seoul, 1989)
This book introduce about weed biology and ecology, weed control, new herbicide and herbicideproperty, weed biology and ecology...
Keywords: Cỏ dại,Weeds; Kiểm soát,Hội nghị,Control,Congresses; Asia